Pendekatan Berbasis Pangan untuk Mengatasi Anemia Kehamilan: Evaluasi Efektivitas Puding Daun Kelor dalam Meningkatkan Kadar Hemoglobin - Arma, Nuriah; Nurrahmaton, Nurrahmaton; Juliani , Sri; Pratiwi , Debby; Wibawanto , Salsabila (Journal of Pharmaceutical and Sciences, 2025)
Background: Anemia in pregnant women increases the risk of complications such as preterm birth and low birth weight. Although iron supplements are the primary treatment, side effects like nausea and constipation often reduce compliance. Moringa leaves (Moringa oleifera), a natural source of iron and vitamin C, show potential as an alternative. The innovation of processing moringa leaves into pudding offers a more appealing, practical, and acceptable solution for pregnant women. Objective: To examine the effect of moringa leaf pudding on increasing hemoglobin (Hb) levels in anemic pregnant women at Pratama Shanti Clinic. Methods: A quasi-experimental study with a one-group pretest-posttest design was conducted. The sample comprised 15 anemic pregnant women selected through purposive sampling. Data were analyzed using the Wilcoxon test. Results: The mean Hb level increased significantly from 9.91 g/dL (pre-intervention) to 11.38 g/dL (post-intervention) (p=0.002). Hb improvement was observed in 86.7% of respondents, with a maximum increase of 2.00 g/dL. Conclusion: Moringa leaf pudding effectively increases Hb levels in anemic pregnant women and can serve as a local food-based nutritional intervention alternative.